Solid catalyst for biodiesel production and Manufacturing method thereof
By supporting inorganic solid catalysts with varying particle sizes and a silica coating on a porous support, the method enhances catalyst loading and active area, addressing leaching and stability issues, thereby improving biodiesel production efficiency.
Patent Information
- Application Number
- KR1020250182471
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-11-26
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2045-11-26
AI Technical Summary
Existing solid catalysts for biodiesel production face limitations such as catalyst leaching and reduced reaction rates upon repeated use, necessitating improvements in loading amount and reaction active area.
A method involving multiple steps of supporting inorganic solid catalysts on a porous support, including a first and second inorganic solid catalyst with different particle sizes and a silica coating to form a core-shell structure, enhancing the catalyst's loading and active area.
The method significantly improves the catalyst's loading and reaction active area, resulting in higher biodiesel yields and maintaining catalytic stability through a composite catalyst with dual functionality.
Smart Images

Figure 112025133098296-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a solid catalyst for biodiesel production and a method for producing the same, and more specifically, to a solid catalyst for biodiesel production in which the loading amount and reaction active area of an inorganic solid catalyst within a porous support are improved, and a method for producing the same. Background Technology
[0002] Interest in biodiesel is continuously increasing as an alternative fuel to reduce dependence on fossil fuels such as oil and coal.
[0003] Biodiesel is obtained through the transesterification and esterification reactions of vegetable oil and waste cooking oil, methanol (or ethanol), and a catalyst (acid or base).
[0004] At this time, catalysts used in biodiesel production are important factors that directly influence the characteristics of transesterification and esterification reactions, and efforts have been made to improve biodiesel yield through catalyst design.
[0005] Liquid acid and base catalysts have the advantage of high reaction efficiency, but they require a complex purification process to remove dissolved catalyst after the reaction, which generates a large amount of wastewater and has limitations in that reuse is impossible.
[0006] Accordingly, active research is underway to develop biodiesel production processes using eco-friendly and reusable solid catalysts to address the problems associated with the use of liquid catalysts.
[0007] However, even in the case of solid catalysts applied to biodiesel, there are limitations such as the leaching of some catalyst components or a decrease in reaction rate and conversion rate upon repeated use; therefore, technology is required to increase the loading amount and reaction active surface area when designing the manufacturing of solid catalysts. The problem to be solved
[0008] The objective of the present invention, which aims to solve the above-mentioned problems, is to provide a solid catalyst for biodiesel production with improved loading amount and reaction active area of an inorganic solid catalyst within a porous support, and a method for manufacturing the same. means of solving the problem
[0009] The method for manufacturing a solid catalyst for biodiesel production according to the present invention for solving the above problem comprises: a first step of immersing and calcining a porous support in a first inorganic solid catalyst precursor solution to produce a porous support on which a first inorganic solid catalyst is supported, and a second step of immersing and calcining the porous support on which the first inorganic solid catalyst is supported in a second inorganic solid catalyst precursor solution to produce a porous support on which a second inorganic solid catalyst is supported.
[0010] The first and second inorganic solid catalysts are characterized by comprising any one of calcium oxide, magnesium oxide, and combinations thereof.
[0011] The above 2nd step is characterized by being performed at a temperature lower than the firing temperature of the 1st step.
[0012] The above-mentioned second inorganic solid catalyst is characterized by having a smaller average particle size than the first inorganic solid catalyst.
[0013] The method is characterized by including a third step, which involves silica coating a porous support on which a second inorganic solid catalyst is supported, and then introducing sulfonic acid groups after the second step.
[0014] The solid catalyst for biodiesel production according to the present invention for solving the above problem is characterized by being produced by the method for producing a solid catalyst for biodiesel production described above. Effects of the invention
[0015] As described above, the solid catalyst for biodiesel production and the method for producing the same according to the present invention have the effect of improving the loading amount of the inorganic solid catalyst and the reaction active area within the porous support. Brief explanation of the drawing
[0016] FIG. 1 is a schematic diagram showing the composition of a solid catalyst for biodiesel production according to the present invention. FIG. 2 is a schematic diagram showing an example of a solid catalyst for biodiesel production according to the present invention. Specific details for implementing the invention
[0017] The specific features and advantages of the present invention will be described in detail below with reference to the accompanying drawings. Prior to this, if it is determined that a detailed description of the functions and configurations related to the present invention may unnecessarily obscure the essence of the invention, such detailed description will be omitted.
[0018] The present invention relates to a solid catalyst for biodiesel production and a method for producing the same, and more specifically, to a solid catalyst for biodiesel production in which the loading amount and reaction active area of an inorganic solid catalyst within a porous support are improved, and a method for producing the same.
[0019] The method for manufacturing a solid catalyst for biodiesel production according to the present invention comprises a first step of immersing and calcining a porous support in a first inorganic solid catalyst precursor solution to produce a porous support on which a first inorganic solid catalyst is supported, and a second step of immersing and calcining the porous support on which the first inorganic solid catalyst is supported in a second inorganic solid catalyst precursor solution to produce a porous support on which a second inorganic solid catalyst is supported.
[0020] Figure 1 shows the composition of a solid catalyst for biodiesel production according to the present invention.
[0021] In step 1 A porous support (100) is immersed in and calcined in a first inorganic solid catalyst precursor solution to produce a porous support on which the first inorganic solid catalyst (200) is supported, and by supporting the inorganic solid catalyst on the porous support, the catalytic activity and catalytic stability can be maintained even during repeated use.
[0022] The porous support (100) may include at least one of alumina (Al2O3) and lanthanum oxide (La2O3), and may have an average particle size of 10 to 150 μm and a porosity of 40 to 60%.
[0023] The first inorganic solid catalyst (200) comprises any one of calcium oxide (CaO), magnesium oxide (MgO), and combinations thereof, and the porous support is immersed in the first inorganic solid catalyst precursor solution and then calcined to produce the first inorganic solid catalyst porous support.
[0024] The calcium oxide precursor may include any one of CaCO3, Ca(OH)2, and Ca(NO3)2, and the magnesium oxide precursor may include MgSO4, MgCl2 and It may include any one of Mg(OH)2.
[0025] At this time, the first inorganic solid catalyst precursor solution may have a viscosity of 150 to 500 cP (at 25°C).
[0026] In the above first step, the firing temperature can be performed at 600 to 1000°C for 2 to 6 hours, and preferably at 800°C to 900°C for 3 to 5 hours.
[0027] If performed under conditions below the above calcination temperature and time, the thermal decomposition of the precursor occurs unevenly and it is difficult to immobilize the first inorganic solid catalyst; and if the above calcination temperature and time are exceeded, the reaction active area is reduced due to the aggregation and growth of particles of the inorganic solid catalyst, resulting in lower catalytic activity, so it is desirable not to exceed the above temperature and time condition range.
[0028] The average particle size of the first inorganic solid catalyst supported on the porous support is 65 to 150 nm.
[0029] In the above second step, the porous support on which the first inorganic solid catalyst is supported is immersed in and calcined in a second inorganic solid catalyst precursor solution to produce a porous support on which the second inorganic solid catalyst (300) is supported.
[0030] In the pores of the porous support on which the first inorganic solid catalyst obtained from the above step 1 is supported, there may be surface regions where the first inorganic solid catalyst is not adsorbed, or empty spaces between the first inorganic solid catalyst particles.
[0031] In the above second step, the amount of catalyst loaded can be improved by filling the non-adsorbent regions and empty spaces of the porous support with a second inorganic solid catalyst.
[0032] The second inorganic solid catalyst may include any one of calcium oxide, magnesium oxide, and combinations thereof. In this case, the calcium oxide precursor may include any one of CaCO3, Ca(OH)2, and Ca(NO3)2, and the magnesium oxide precursor may include MgSO4, MgCl2 and It may include any one of Mg(OH)2.
[0033] At this time, the second inorganic solid catalyst is formed to have a smaller average particle size than the first inorganic solid catalyst so that it fills the spaces between the particles of the first inorganic solid catalyst and the unadsorbed regions of the porous support, thereby maximizing the loading amount of the inorganic solid catalyst and further increasing the reaction active area.
[0034] In order to form a small average particle size of the second inorganic solid catalyst, the second inorganic solid catalyst precursor solution may include any one of citric acid, polyethylene glycol, ethylenediaminetetraacetic acid, and combinations thereof.
[0035] The above additive can form the size of the second inorganic solid catalyst particles smaller than that of the first inorganic solid catalyst particles by inhibiting the aggregation and growth of the second inorganic solid catalyst particles. In addition, the above additive can further improve the adsorption characteristics of the first inorganic solid catalyst particles and the second inorganic solid catalyst particles on a porous support, thereby minimizing loss and leaching due to repeated use.
[0036] The above additive may be included in an amount of 20 to 40 wt% of 100 wt% of the second inorganic solid catalyst precursor solution. It is desirable not to exceed the above addition range, as if the amount of the additive is less than 20 wt%, the effect is negligible, and if it is added in an amount of 40 wt% or more, the remaining additive acts as an impurity, closing the pores of the porous support and reducing the reaction active area.
[0037] The second inorganic solid catalyst precursor solution is used having a viscosity of 30 to 150 cP (at 25°C), which improves flowability and penetration between the porous support pores and the first inorganic solid catalyst particles, and enables thin film coating and uniform loading.
[0038] At this time, the average particle size of the second inorganic solid catalyst is not limited as long as it is smaller than the average particle size of the first inorganic solid catalyst, but preferably, it has an average particle size of 1 to 50 nm.
[0039] In the above second step, the firing is performed at a temperature lower than the firing temperature of the first step, thereby preventing the regrowth of the first inorganic solid catalyst particles and the aggregation and bonding with adjacent second inorganic solid catalysts, and preventing excessive particle growth of the second inorganic solid catalyst.
[0040] In the second step, the firing temperature may be 400 to 800°C for 1 to 5 hours, and preferably 450 to 750°C for 2 to 4 hours. Alternatively, the firing temperature may be gradually increased to 400 to 800°C at a heating rate of 1 to 3°C per minute, and then 1 to 5 hours at the maximum temperature.
[0041] Thus, the solid catalyst for biodiesel production according to the present invention has a first inorganic solid catalyst and a second inorganic solid catalyst having a double particle size distribution supported on a porous support, and the second inorganic solid catalyst has a smaller average particle size than the first inorganic solid catalyst and is filled in the unadsorbed regions and empty spaces within the pores of the porous support, thereby increasing the amount of solid catalyst loaded and further improving the reaction active area, resulting in excellent yield.
[0042] In addition, the method for manufacturing a solid catalyst for biodiesel production according to the present invention may include a third step of introducing an acid functional group onto a porous support on which the first and second inorganic solid catalysts are supported, in order to have dual functionality as an acid-base composite catalyst after performing the second step.
[0043] FIG. 2 shows an example in which a silica coating film and an acid functional group are introduced into a solid catalyst for biodiesel production according to the present invention.
[0044] In the above 3rd step, a porous support supported with a second inorganic solid catalyst, which is a solid base catalyst, is coated with a silica coating solution to form a silica coating film (400), and a sulfonic acid group, which is an acid functional group (500), is introduced into the formed silica coating film so that it can function as an acid-base composite catalyst, and the acid-base composite catalyst has a core-shell structure.
[0045] At this time, the silica coating film serves as a support for introducing sulfonic acid groups, while simultaneously preventing the catalytic effect from being canceled out by the direct proximity of the acid and base catalysts and improving catalyst stability.
[0046] A method of coating a porous support supported with a second inorganic solid catalyst with a silica coating solution can be performed by modifying the Stober method.
[0047] The above silica coating solution comprises a solvent, ammonium hydroxide, and tetraethyl orthosilicate (TEOS). A porous support (core material) on which a second inorganic solid catalyst is supported is dispersed in the solvent and ammonium hydroxide by means such as ultrasound and stirring, and then tetraethyl orthosilicate (TEOS) is added to produce a structure having a core (porous support on which the second inorganic solid catalyst is supported)-shell (silica coating film) structure.
[0048] Subsequently, a thiolized structure is prepared by introducing a thiol group (-SH) into the above structure in the first step, and then the surface thiol group is converted into a sulfonic acid group (-SO3H) by treating it with hydrogen peroxide (H2O2) in the second step.
[0049] At this time, the precursor for introducing the thiol group may include any one of 3-Mercaptopropyltrimethoxysilane (MPTMS), 3-Mercaptopropyltriethoxysilane (MPTS), and combinations thereof.
[0050] Hereinafter, the solid catalyst for biodiesel production according to the present invention is manufactured by the method for manufacturing a solid catalyst for biodiesel production described above, and a detailed description thereof is omitted as it has been described above.
[0051] The solid catalyst for biodiesel production according to the present invention comprises a first inorganic solid catalyst and a second inorganic solid catalyst having a double particle size distribution supported on a porous support, wherein the second inorganic solid catalyst has a smaller average particle size than the first inorganic solid catalyst and is filled into the unadsorbed regions and empty spaces within the pores of the porous support, thereby increasing the amount of solid catalyst loaded and further enhancing the reaction active area, resulting in excellent yield.
[0052] In addition, the solid catalyst for biodiesel production according to the present invention can function as a composite catalyst with acid-base dual functionality having a core-shell structure by introducing a silica coating film and an acid functional group on a porous support on which the first and second inorganic solid catalysts are supported.
[0053] Hereinafter, a method for producing biodiesel using a solid catalyst for biodiesel production according to the present invention (hereinafter abbreviated as "method for producing biodiesel") will be described.
[0054] The method for producing biodiesel according to the present invention utilizes a solid catalyst for producing biodiesel produced by the method described above, wherein the mixture of oil, alcohol, and the solid catalyst for producing biodiesel is reacted at 20 to 80°C for 60 seconds to 18 hours, wherein the molar ratio of the oil to the alcohol is 1:4 to 12, and the solid catalyst for producing biodiesel is added in an amount of 0.5 to 15 weight% relative to the weight of the oil.
[0055] The above oil may be any one of the group consisting of soybean oil, rapeseed oil, corn oil, rapeseed oil, sunflower oil, castor oil, palm oil, linseed oil, poppy oil, walnut oil, peanut oil, cottonseed oil, rice bran oil, camellia oil, olive oil, jatropha oil, perilla oil, sesame oil, fish oil, lard, beef tallow, beef brisket, chicken fat, waste oil with an increased acid value due to repeated use of these, and combinations thereof.
[0056] The above alcohol may be selected from those commonly used, and is not particularly limited thereto, but one or more selected from the group consisting of alcohols having 1 to 5 carbon atoms may be used. Specific examples of the above alcohol include one or more selected from methanol, ethanol, propanol, isopropanol, and butanol, and a mixture thereof. Preferably, any one of methanol, ethanol, and combinations thereof may be used.
[0057] It is preferable to react at a temperature of 20 to 80°C for 60 seconds to 18 hours. If the reaction temperature and reaction time are below the above range, the reaction activity and the conversion rate of the alkyl ester are low. If the reaction is above the above range, the conversion efficiency is lowered due to the evaporation of alcohols having a low boiling point (60 to 80°C), and the increase in reactivity with increasing temperature and time is negligible, so it is preferable not to exceed the above range.
[0058] The above alcohol is mixed with oil to induce transesterification, wherein the molar ratio of oil to alcohol is preferably 1:4 to 12, and if the molar ratio is less than 1:4, the production yield of the alkyl ester decreases, and if it exceeds 1:12, purification becomes difficult due to the increased solubility of glycerin in alcohol, and the glycerin generated during the reaction reverses the reaction, causing a decrease in the yield of the alkyl ester (biodiesel).
[0059] The above-mentioned solid catalyst for biodiesel production is added in an amount of 0.5 to 15 weight percent relative to the weight of the oil. If the above-mentioned solid catalyst is added in an amount less than 0.5 weight percent relative to the weight of the oil, it is inefficient because it is difficult to cause esterification reactions and transesterification reactions or the biodiesel conversion rate is low. If it is added in an amount exceeding 15 weight percent, the increase in catalytic effect due to the increase in the amount of catalyst is negligible, so it is desirable not to exceed the above range.
[0060] The present invention will be described in detail below with reference to a preferred embodiment. However, the following embodiment is intended to specifically illustrate the present invention and is not limited thereto.
[0061] 1. Preparation of catalyst
[0062] Catalyst A
[0063] Alumina (Al2O3) powder (average particle size 80 μm, porosity 55%) was prepared as a porous support. Ca(NO3)2 was prepared as the first inorganic catalyst precursor, and 50 g of the prepared alumina (Al2O3) powder was immersed in 200 mL of a 1 M aqueous solution of Ca(NO3)2. Subsequently, the mixture was stirred and impregnated at 50 rpm for 6 hours at 25°C, dried at 100°C for 12 hours, and then calcined at 800°C for 4 hours to obtain a support (catalyst A) loaded with CaO. The average particle size of the loaded CaO in the obtained catalyst A was confirmed to be approximately 95 nm, and the specific surface area was 102 m². 2 It was confirmed as / g.
[0064] Catalyst B
[0065] Ca(NO3)2 was prepared as a second inorganic catalyst precursor, and ethylenediaminetetraacetic acid (EDTA) was prepared as an additive to introduce a smaller-sized second inorganic catalyst into the pores of catalyst A. At this time, 28 g of EDTA was added per 100 g of a 1 M aqueous solution of Ca(NO3)2, and the solution was dispersed for 15 minutes using a 28 kHz ultrasonic disperser. The viscosity of the prepared second inorganic catalyst precursor solution was 57 cP.
[0066] 15 g of catalyst A was added to 200 ml of the prepared second inorganic catalyst precursor solution and stirred for 3 hours, followed by drying at 110°C for 10 hours and calcination at 700°C for 3 hours to obtain catalyst B supported with the second inorganic solid catalyst. As a result, the additional CaO introduced into the obtained catalyst B was confirmed to have an average particle size of approximately 41 nm and a specific surface area of 156 m². 2 It was confirmed as / g.
[0067] Catalyst B-1
[0068] To determine the effect of the use or absence of additives on the average particle size of additionally introduced CaO without additives A second inorganic catalyst precursor solution was prepared. Except for the additive, the remaining conditions were carried out identically to the preparation process of catalyst B.
[0069] Ca(NO3)2 was prepared as the second inorganic catalyst precursor. 15 g of catalyst A was added to 200 ml of the prepared second inorganic catalyst precursor solution and stirred for 3 hours. The mixture was then dried at 110°C for 10 hours and calcined at 700°C for 3 hours to obtain catalyst B-1, which supports the second inorganic solid catalyst. It was difficult to distinguish between the second inorganic catalyst CaO additionally introduced into the obtained catalyst B-1 and the first inorganic catalyst present in catalyst A; from this, it could be inferred that the additive reduced the size of the second inorganic catalyst. Furthermore, regarding the specific surface area, it was 112 m² 2 The specific surface area was measured to be slightly higher than that of catalyst A at / g, but the improvement in specific surface area compared to catalyst B was negligible.
[0070] Catalyst B-2
[0071] MgCl2 was prepared as the second inorganic catalyst precursor, and ethylenediaminetetraacetic acid (EDTA) was prepared as an additive. At this time, 28 g of EDTA was added per 100 g of 1 M aqueous MgCl2 solution, and the mixture was dispersed for 15 minutes using a 28 kHz ultrasonic disperser. The viscosity of the prepared second inorganic catalyst precursor solution was 62 cP.
[0072] 15 g of catalyst A was added to 200 ml of the prepared second inorganic catalyst precursor (MgCl2) solution and stirred for 3 hours, followed by drying at 110°C for 10 hours and calcination at 700°C for 3 hours to obtain catalyst B-2 supported with the second inorganic solid catalyst. As a result, the average particle size of the additionally introduced MgO in the obtained catalyst B was confirmed to be approximately 32 nm, and the specific surface area was 163 m². 2 It was confirmed to be / g. For the subsequent process, catalyst B-2, which has an excellent specific surface area, was used.
[0073] Catalyst C
[0074] After forming a silica coating film on catalyst B-2, an acid-base dual-functional composite catalyst was prepared by introducing sulfonic acid groups.
[0075] Catalyst B-2 was added to a solvent of ethanol:ammonium hydroxide:water = 6:1:1 (volume ratio) and stirred, followed by the dropwise addition of TEOS and further stirring. Subsequently, 0.5 mL of 3-mercaptopropyltrimethoxysilane (MPTMS) was added and reacted at 40°C for 4 hours, after which sulfonic acid groups (-SO₃H) were introduced by oxidizing with hydrogen peroxide (30%) for 2 hours. The specific surface area of the prepared catalyst C was 138 m². 2 It was confirmed as / g.
[0076] 2. Production of biodiesel using catalysts
[0077] Soybean oil was prepared as the reaction composition, and its acid value was confirmed to be 11 mg KOH / g. 100 g of soybean oil and 30 g of methanol (molar ratio to oil 1:6) were added to a 500 mL three-necked flask. A stirrer, a reflux condenser, and a thermometer were attached, and catalysts A, B, B-2, and C were added at 1.0 wt% relative to the weight of the oil, respectively. The reaction mixture was heated to 60°C and stirred at 600 rpm, and the transesterification reaction was carried out for 6 hours. After the reaction was complete, the catalysts were removed by filtration, and the methanol was removed from the product by vacuum distillation. The supernatant was separated to obtain biodiesel (methyl ester) and glycerin layers. The methyl ester content of the resulting biodiesel was quantified using GC-FID to determine the conversion rate. In addition, to verify the feasibility of repeated catalyst use, the conversion rate was calculated after three repeated uses. The catalyst used at this time was washed (ethanol), dried at 110°C for 12 hours, and then reused.
[0078] Table 1 below shows the conversion rate according to the catalyst and the conversion rate after 3 repeated uses.
[0079] catalyst Conversion rate % (per time) Conversion rate after 3 repeated uses Catalyst A 84.7 79.51 Catalyst B 91.2 87.4 Catalyst B-2 93.4 90.7 Catalyst C 96.5 93.8
[0080] As shown in [Table 1], there was a distinct difference in the biodiesel conversion rate depending on the type of catalyst.
[0081] Catalyst A was found to have the lowest conversion rate at 84.7%, whereas catalyst B, prepared by additionally supporting a second inorganic catalyst (CaO) using the same support and treating with EDTA, showed an improved conversion rate of 91.2%. This is interpreted as a result of the reaction active area being expanded through additional support and the reaction efficiency being improved through the finer formation of CaO particles.
[0082] In the case of catalyst B-2, which used MgO as the second inorganic catalyst, the conversion rate was 93.4%, which was found to be higher than that of catalyst B. It was determined that the conversion rate was improved due to the interaction between the two types of inorganic catalysts.
[0083] The highest conversion rate was confirmed in catalyst C, which has an acid-base dual function, showing a conversion rate of 96.5%. This is interpreted as a result of the introduction of a silica coating film and sulfonic acid groups enabling a combined acid-base reaction, which simultaneously promoted esterification and transesterification reactions even in high acid value oils with an acid value of 11 mg KOH / g.
[0084] When examining the conversion rate after repeated use, catalyst A, a single basic catalyst, showed a decrease in conversion rate from 84.7% after one reaction to 79.5% after three repeated uses, confirming that the loss of structural stability and surface active sites was relatively large. In contrast, catalyst B showed a gradual decrease from 91.2% after one reaction to 87.4% after three, and catalyst B-2 showed a gradual decrease from 93.4% after one reaction to 90.7% after three.
[0085] This is believed to be the result of suppressing catalyst particle detachment and sintering through a double support structure and the introduction of fine particles. The best durability was observed in catalyst C, which maintained a high conversion rate of 93.8% even after three cycles compared to 96.5% after one cycle. This is interpreted as being due to the silica coating layer preventing structural damage to the catalyst and maintaining the chemical stability of the sulfonic acid group (-SO₃H) even during repeated reactions.
[0086] As described above, although the present invention has been explained with reference to the attached drawings and with reference to preferred embodiments, those skilled in the art may modify or vary the present invention in various ways without departing from the technical spirit and scope described in the claims of the present invention. Accordingly, the scope of the present invention should be interpreted by the claims described to include such many variations. Explanation of the symbols
[0087] 100: Porous support 110: Pores of the porous support 200: First inorganic solid catalyst 300: Second inorganic solid catalyst 400: Silica coating film 500: Acid function
Claims
Claim 1 A method for manufacturing a solid catalyst for biodiesel production, comprising: a first step of preparing a porous support supported with a first inorganic solid catalyst by immersing and calcining the porous support supported with the first inorganic solid catalyst in a first inorganic solid catalyst precursor solution; a second step of preparing a porous support supported with a second inorganic solid catalyst by immersing and calcining the porous support supported with the first inorganic solid catalyst in a second inorganic solid catalyst precursor solution; and a third step of forming a core-shell structure in which the porous support supported with the second inorganic solid catalyst is used as a core and a silica coating film is used as a shell, and then introducing sulfonic acid groups into the silica coating film to form an acid-base composite catalyst, wherein the second inorganic solid catalyst is formed with an average particle size smaller than that of the first inorganic solid catalyst and is filled into the empty spaces between the particles of the first inorganic solid catalyst and the unadsorbed regions of the porous support. Claim 2 A method for manufacturing a solid catalyst for biodiesel production according to claim 1, wherein the first inorganic solid catalyst and the second inorganic solid catalyst comprise any one of calcium oxide, magnesium oxide, and combinations thereof. Claim 3 A method for manufacturing a solid catalyst for biodiesel production according to claim 1, characterized in that the calcination in the second step is performed at a temperature lower than the calcination temperature of the first step. Claim 4 delete Claim 5 delete Claim 6 A solid catalyst for biodiesel production characterized by being produced by a method for producing a solid catalyst for biodiesel production according to any one of claims 1 to 3.
Citation Information
Patent Citations
Load type calcium oxide catalyst, its preparation method and uses
CN1836772A
